Impact of Solvent Evaporation and Curing Protocol on Degree of Conversion of Etch-and-Rinse and Multimode Adhesives Systems - Ceci Nunes Carvalho; Marcos Daniel Septímio Lanza; Letícia Gomes Dourado; Edilausson Moreno Carvalho; José Bauer (International Journal of Dentistry)
Objectives. This study evaluated the effect of air-drying time and light-curing time on the degree of conversion (DC) of three etch-and-rinse adhesive systems: ONE-STEP (OS) and ONE-STEP plus (OSP), Ambar (AMB), and two multimode adhesive systems: All-Bond Universal (ABU) and ScotchBond Universal (SBU) by Fourier transform infrared (FTIR) analysis. Materials and Methods. The DC of each adhesive system was analyzed with six experimental different protocols: (1) immediate light curing for 10 s without solvent volatilization; (2) 10 s solvent volatilization with air stream plus 10 s light curing; (3) 60 s solvent volatilization with air stream plus 10 s light curing; (4) immediate light curing for 20 s without solvent volatilization; (5) 10 s solvent volatilization with air stream plus 20 s light curing; and (6) 60 s solvent volatilization with air stream plus 20 s light curing. FTIR spectra were obtained, and the DC was calculated by comparing the ratio of aliphatic/aromatic double carbon bonds before and after light activation (Bluephase 20i). The DC means were analyzed by three-way analysis of variance (ANOVA) and post hoc Tukey tests (α = 0.05). Results. Three-way ANOVA showed statistically significant adhesive, air-drying, and light-cured time (p<0.001). In general, there was a trend of increased DC when the adhesives were dried and cured for longer times, but that was not observed for all the adhesives tested. The acetone-based adhesive systems require an air-drying prior to light activation. The light-curing time of 20 s increases the DC of all materials tested. Conclusion. The results suggested that the DC of the adhesive systems tested was material dependent. In general, the protocol with solvent evaporation for 10 seconds with air syringe plus 20 seconds of light curing finds the high values of DC.